Industria de los periódicos y Sociedad de la Información en España - Larrañaga Rubio, Julio (Estudios sobre el Mensaje Periodístico, 2008)
Newspaper industry is a mature industry with low yearly increases of its main economic data. The ITCs are on the other hand furthering an increased loss of readers, especially among the youngest. And from different institutional quarters a more intensive use of Internet is voiced as a means to recover the audience and increase incomes through advertising. The use of all the possibilities of the Web 2.0 is also under recommendation as well as introducing multimedia to contents. The low penetration level of Information Society in Spain acts as an obstacle in the development of the industry. Thus political decisions and measures are a necessary requirement to futher future developments.
Keywords: Newspaper industry; Information Society; Web 2; multimedia content; newspapers online